Novel rechargeable calcium phosphate dental nanocomposite - Zhang, Ling; Weir, Michael D.; Chow, Laurence C.; Antonucci, Joseph M.; Chen, Jihua; Xu, Hockin H.K. (Dental materials, 2016)
Calcium phosphate (CaP) composites with Ca and P ion release can remineralize tooth lesions and inhibit caries. But the ion release lasts only a few months. The objectives of this study were to develop rechargeable CaP dental composite for the first time, and investigate the Ca and P recharge and re-release of composites with nanoparticles of amorphous calcium phosphate (NACP) to achieve long-term inhibition of caries. Three NACP nanocomposites were fabricated with resin matrix of: (1) bisphenol A glycidyl dimethacrylate (BisGMA) and triethylene glycol dimethacrylate (TEGDMA) at 1:1 mass ratio (referred to as BT group); (2) pyromellitic glycerol dimethacrylate (PMGDM) and ethoxylated bisphenol A dimethacrylate (EBPADMA) at 1:1 ratio (PE group); (3) BisGMA, TEGDMA, and Bis[2-(methacryloyloxy)ethyl] phosphate (BisMEP) at 2:1:1 ratio (BTM group). Each resin was filled with 20% NACP and 50% glass particles, and the composite was photo-cured. Specimens were tested for flexural strength and elastic modulus, Ca and P ion release, and Ca and P ion recharge and re-release. NACP nanocomposites had strengths 3-fold of, and elastic moduli similar to, commercial resin-modified glass ionomer controls. CaP ion recharge capability was the greatest for PE group, followed by BTM group, with BT group being the lowest (p<0.05). For each recharge cycle, CaP re-release reached similarly high levels, showing that CaP re-release did not decrease with more recharge cycles. After six recharge/re-release cycles, NACP nanocomposites without further recharge had continuous CaP ion release for 42 d. Novel rechargeable CaP composites achieved long-term and sustained Ca and P ion release. Rechargeable NACP nanocomposite is promising for caries-inhibiting restorations, and the Ca and P ion recharge and re-release method has wide applicability to dental composites, adhesives, cements and sealants to achieve long-term caries-inhibition.